Performance Analysis of Some Batch Verification Methods of Digital Signatures - Guan, D. J.; Zhuang, E. S.; Chung, I. C.; Yu-Shen Lin (2017 12th Asia Joint Conference on Information Security (AsiaJCIS), 2017)
In this paper, we compare three methods in detecting invalid signatures in batch verification. The first method, randomly select test, randomly chooses a half of signatures to verify in a batch. The second method is the small exponent test which is widely used. The third method, randomly numbering test, is a simplified method of the matrix-detection algorithm. The randomly numbering test randomizes the order of the signatures and verifies the signatures in log k+1 batches where k is the number of signatures. We simulate each method and analyze the efficiency of the methods. As a result, randomly numbering test is more efficient than small exponent test when the number of signatures in a batch verification is large.